Global Mapping Analysis of Maxillofacial Trauma Literature From 1980-2022 - Balel, Yunus (European Journal of Therapeutics, 2023)
Objective: The study is aimed to make a comprehensive bibliometric analysis of the literature in the field of maxillofacial trauma (MFT), to determine the focal points and to present the results in a simplified manner by using various mapping methods. In addition, it is aimed to determine the important articles that constitute the main backbone of the MFT literature with objective methods and to provide a source for education and new studies in this field. Methods: The publications related to maxillofacial traumas between 1980-2022 using the search terms "injury, trauma, fracture, facial, mandible, mandibular, nasal, midface, orbit, ocular, maxilla, maxillary" were obtained from the Web of Science Core Collection database. Nodes and connections were created using CiteSpace software to create the maps used in the visualization. Cooperation between countries, distribution of topics, co-citation, co-citation clustering analysis were applied. Results: There were 8850 publications and 78216 references. The MFT literature was divided into a total of 16 clusters. The most published topic was about mandible fractures. While there was a very strong correlation between the country's gross national product and the number of publications (R=0.886), there was a moderate correlation between the country's population and the number of publications (R=0.403). Conclusion: In the presented study, the forty-years history of the MFT literature was evaluated with bibliometric analysis methods; the most influential publications, the topics in which the literature is divided and hot spots were determined.